Self-limiting robust surface-grafted organic nanofilms - Todd Banner, L. (2010)
Robust surface-bound insulating polymer films with controlled thickness in <5 nm range are important for technological advances in diverse disciplines such as electrochemical sensors, molecular electronics, separations, and anticorrosive coatings. Creating these films by simple methods from readily available materials has been a significant challenge. Here we report a newly synthesized molecule combining styrene and thiol moieties, joined via a short linker, that binds to the gold surface, polymerizes, and cross-links polymer chains to form robust films with uniform and controlled thickness and complete surface coverage. Additional layers can be deposited. These films that bridge two- and three-dimensional materials show excellent stability and insulating properties.